2013
DOI: 10.1007/s10528-012-9559-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Variability among Isolates of Fusarium oxysporum Associated with Root Rot Disease of Agave tequilana

Abstract: In this study, 115 isolates of Fusarium oxysporum from roots of Agave tequilana Weber cv azul plants and soil in commercial plantations in western Mexico were characterized using morphological and molecular methods. Genetic analyses of monosporic isolates included restriction enzyme analysis of rDNA (ARDRA) using HaeIII and HinfI, and genetic diversity was determined using Box-PCR molecular markers. Box-PCR analysis generated 14 groups. The groups correlated highly with the geographic location of the isolate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 6 publications
0
15
0
6
Order By: Relevance
“…Agave diseases can reduce the normal growth of the plant, or even cause the death of this (Rubio, ). It also have been reported the occurrence of other fungal genera as Cercospora , Asterina , Colletotrichum and Alternaria (Jiménez‐Hidalgo et al, ; Vega‐Ramos et al, ). However, little is known about of the damage that these microorganisms could cause to Agave plants (Desgarennes et al, ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Agave diseases can reduce the normal growth of the plant, or even cause the death of this (Rubio, ). It also have been reported the occurrence of other fungal genera as Cercospora , Asterina , Colletotrichum and Alternaria (Jiménez‐Hidalgo et al, ; Vega‐Ramos et al, ). However, little is known about of the damage that these microorganisms could cause to Agave plants (Desgarennes et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that A. tequilana suffers a phytosanitary crisis, in which large amounts of plants are lost due to the presence of several phytopathogens, and the symptoms that occur are abnormal curl of the leaves, necrosis, wilting of the leaves and death of the whole plant (Castro‐Valera, ). It has been proposed that the causal agent of these diseases is Fusarium oxysporum (Rubio, ; Vega‐Ramos et al, ). Agave diseases can reduce the normal growth of the plant, or even cause the death of this (Rubio, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El incremento en la superficie del cultivo potencialmente podría incrementar la incidencia de enfermedades como ha sucedido en plantaciones de A. tequilana (Ávi-la-Miranda et al, 2010). La marchitez causada por el hongo fitopatógeno Fusarium oxysporum es uno de los problemas fitosanitarios que afecta significativamente la productividad del agave tequilero; el proceso de infección se inicia en las raíces, posteriormente se observa un enrollamiento y muerte en las puntas de las hojas, que culmina con la marchitez de toda la planta (Vega-Ramos et al, 2013). Esta problemática fitosanitaria también se presenta en plantaciones de A. cupreata en el estado de Michoacán.…”
Section: Fully Bilingualunclassified
“…Los HMA forman simbiosis con alrededor de 80 % de las plantas terrestres. En esta asociación, las hifas simbióticas del hongo micorrícico transportan nutrientes del suelo hacia la followed by the tips of leaves curling and dying, and finally, the entire plant wilts (Vega-Ramos et al, 2013). This plant health problem also appears in A. cupreata plantations in the state of Michoacán.…”
Section: Fully Bilingualunclassified